Eating disorders in relation to alcohol addiction—A study of drunkorexia in young adults in Poland - Giezek, Marta; Landowski, Marek; Zabielska, Paulina; Szpakow, Andriej; Karakiewicz, Beata (Frontiers in Public Health, 2025)
IntroductionThe aim of the study was to determine the frequency of eating disorders occurring in combination with alcohol dependence in young adults in Poland.Material and methodsThe study was conducted in Poland between 1st July 2023 and 31st July 2024. The diagnostic survey method was applied. The following tests were used to identify problems: AUDIT (Alcohol Use Disorders Identification Test) for assessing alcohol consumption, drinking behaviors, and alcohol-related problems, and EAT 26 (Eating Attitudes Test) for the psychometric assessment of eating disorders.ResultsStatistical analysis of the average AUDIT and EAT-26 survey scores according to gender and age (under 25 years and from 25 to 35 years) revealed a statistically significant difference in results between the male and female groups. The average AUDIT survey score for women was lower than for men and amounted to 4.42 and 6.77, respectively. This might indicate that men engage in alcohol consumption more frequently than women. However, for the EAT-26 survey, the situation was the opposite, an average score was higher for women than for men and amounted to 10.7 and 6.71, respectively. In this case, this result could indicate that women have a greater tendency to eating disorders or that women more frequently use weight loss diets than men. The study group included young adults with an AUDIT score greater than or equal to 15, which indicates the probability of alcohol addiction. As many as 80.95% of women and 44% of men from this group might also suffer from eating disorders.ConclusionsThe article draws attention to a relatively new, especially in Poland, public health problem which requires the introduction of appropriate preventive measures, particularly in the area of raising awareness of the negative effects of treating alcohol as a regulator of emotions and in the area of nutritional education. The research results and the description of the problem are a useful contribution to the practice of doctors and nurses in primary health care allowing them to differentiate drunkorexia from alcoholism and eating disorders and introduce early therapeutic procedures in order to prevent serious health and social consequences.